Association of physical activity level and physical fitness with the cognitive function of patients in hemodialysis - Waldow Kupske, Juliedy; Severo Dutra, Thaís; Firpo Del Duca, Giovani; Pimentel Ferreira, Aparecido; Ricardo Moreira, Paulo; Marchesan Krug, Moane; de Rosso Krug, Rodrigo (Pensando Psicología, 2023)
This study aimed to correlate cognitive function with the physical activity level (pal) and physical fitness over three years of patients undergoing hemodialysis and to compare the pal and physical fitness over this period of patients with and without cognitive problems. Therefore, a cohort study was carried out, including patients evaluated between 2018 and 2020, through the Mini-Mental State Exam, functional physical record, Elbow Flexion test, Sit-to-stand test, Handgrip Strength test (hgs), and by the physical activity monitor. Data analysis was performed using the Pearson’s Correlation test and the paired Student’s t-test and its non-parametric equivalent, when necessary, with a significance level of 5%. The results showed that cognitive function assessed in the different years of the research was positively correlated with physical fitness and with pal: in 2018, with hgs (r = 0.313; p = 0.019); in 2019, with cardiorespiratory fitness (r = 0.288; p = 0.038), with hgs (r = 235; p = 0.033) and with pal on hd days (r = 359; p = 0.010) and on days without treatment (r = 314; p = 0.026); and in 2020, with the pal up to date without hd (r = 387; p = 0.014). In addition, patients without probable cognitive deficit had higher pal and physical fitness values in all years of analysis compared to those with the probable cognitive deficit: in 2018, this difference was significant in hgs and pal on a day contrary to hemodialysis; in 2019, in cardiorespiratory fitness and pal on a day contrary to treatment; and in 2020, in cardiorespiratory fitness, hgs and pal on both days. It is concluded that patients with higher pal and better physical fitness had a better cognitive function, suggesting the importance of physical activity practice as an effective alternative in improving physical fitness and, consequently, cognitive function in HD patients.
Keywords: Chronic Renal Failure; Musculoskeletal and Neural Physiological Phenomena; Physical Functional Performance; Motor Activity; Cognition